Racismo no Brasil : contribuições da teologia afrodiaspórica para uma consciência e prática eclesial antirracista - Silva, Tiago da (2023)
The present work intends to understand the elements of the afrodiasporic theologi-cal reflection that he created for an anti-racist ecclesial conscience and practice. First, the research will point out the characteristics of racism in Brazil and capitalism that lead to its perpetuation. Continuing, it will analyze how the relationship between the Church and the black community was constituted in the course of the history of Brazil. Finally, it will indicate the elements of Afrodiasporic Theology that can contri-bute to an antiracist ecclesial awareness and practice. The theme is enriched by the expressive dialogue it establishes with the areas of history and sociology. The the-me is current and relevant, portraying from the perspective of the Church and theo-logy, a social malaise that impacts the lives of millions of Brazilians who cry out for justice and liberation, seeking tocollaborate in the public debate on the anti-racist issue, which is evangelical and prophetic.